An Action Environment - Brand, Mark van den; Iversen, Jørgen; Mosses, Peter D. (BRICS Report Series, 2004)
Some basic programming constructs (e.g., conditional statements) are found in many different programming languages, and can often be included without change when a new language is designed. When writing a semantic description of a language, however, it is usually not possible to reuse parts of previous descriptions without change. This paper introduces a new formalism, ASDF, which has been designed specifically for giving reusable action semantic descriptions of individual language constructs. An initial case study in the use of ASDF has already provided reusable descriptions of all the basic constructs underlying Core ML. The paper also describes the Action Environment, a new environment supporting use and validation of ASDF descriptions. The Action Environment has been implemented on top of the ASF+SDF Meta-Environment, exploiting recent advances in techniques for integration of different formalisms, and inheriting all the main features of the Meta-Environment.